Validating and prioritizing prenatal breastfeeding education recommendations: A nominal group technique study with postnatal mothers and healthcare professionals - Jennifer Kehinde; Claire O’Donnell; Annmarie Grealish (PLoS ONE, 2025)
Introduction Ireland has the lowest breastfeeding rates in Europe, with only 60% of mothers initiating breastfeeding after giving birth, a figure that drops to 43% three months later, highlighting challenges in promoting the initiation and continuation of breastfeeding due to inadequate antenatal breastfeeding education. Our previous qualitative study revealed a disconnect between idealized prenatal breastfeeding educational approaches and the realities of maternal breastfeeding experiences, prompting a call for practical, interactive education that addresses emotional resilience, societal dynamics, and partner involvement. This study refines and prioritizes these recommendations using the Nominal Group Technique, providing insights for integrating practical content, interactive strategies, and standardized guidance into frameworks aligned with the WHO’s 10 Steps to Successful Breastfeeding. Methods This study utilized the Nominal Group Technique to prioritize and evaluate recommendations for improving prenatal breastfeeding education in Ireland, gathering insights from separate sessions with postnatal mothers (n = 6) and healthcare professionals (n = 4). Data analysis was performed using Ritchie’s framework for qualitative content analysis and conducted with NVivo (Version 14; QSR, 2024). The study adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) to ensure transparency and rigor in its reporting. Results This study identified key recommendations for improving prenatal breastfeeding education through a consensus-building process involving postpartum mothers and healthcare professionals. Mothers emphasized the importance of a balanced approach, including benefits, challenges, and mental support, advocating for personalized learning, interactive group sessions, and standardized guidance. They also highlighted the need for partner involvement and strategies to address societal breastfeeding barriers. Healthcare professionals evaluated the feasibility of integrating these recommendations into Ireland’s existing prenatal breastfeeding education framework and their alignment with the WHO’s 10 Steps to Successful Breastfeeding. They endorsed the inclusion of balanced educational content and suggested flexible methods, such as recorded sessions, to encourage partner participation and public breastfeeding support. Although there were some differences in implementation strategies, both groups recognized the importance of these recommendations, offering valuable insights for improving prenatal breastfeeding education frameworks. Conclusion This study highlights the critical need to advance prenatal breastfeeding education in a manner that more effectively supports postnatal mothers while maintaining coherence with existing healthcare frameworks. Findings illustrate a shared commitment among postnatal mothers and healthcare professionals to adopt a more balanced educational model that integrates emotional preparedness, personalized learning pathways, and consistent, standardized messaging. By advocating for the inclusion of partner engagement and addressing broader societal challenges, such as breastfeeding in public, the study promotes a comprehensive and contextually responsive approach to improving maternal and infant health outcomes. Grounded in the WHO’s 10 Steps to Successful Breastfeeding, the study provides actionable, evidence-based recommendations for enhancing the delivery of prenatal breastfeeding education within the Irish health system.